Proses Sosialisasi dan Feedback Warga Terhadap Pembangunan Jalan Tol Yogyakarta – Solo - Aditia Galih Purnama; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
The toll road development is a government program in an effort to equalize development in Indonesia. The development of toll road infrastructure, one of which is the Yogyakarta - Solo Toll Road, it is an important element in accelerating population mobility, and has a positive impact on economic development and growth. This study aims to describe what the team and community responses are doing in the process of disseminating compensation for land acquisition for the construction of the Yogyakarta - Solo Toll Road, and describing the community feedback to see what the team and the community are doing in socialization of the Yogyakarta – Solo Toll Road. The research method uses descriptive qualitative with primary data sources from interviewees as many as 6 people, secondary data was taken from relevant documents, as for data analysis used ethnography. 2 The results of the study show: (1) Socialization was carried out by the preparation team without discussing the price of compensation. (2) the community is very enthusiastic and has approved the construction of the Yogyakata - Solo Toll Road. (3) Community feedback on the socialization of the construction Yogyakarta - Solo Toll Road